Superfine copper guanidine nitrate urea and its synthesis method and application in automobile safety airbag gas generating agent
Patent Information
- Application Number
- CN202611129563.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-20
AI Technical Summary
[0011]本发明的目的是解决现有硝酸脒基脲铜产物粒度偏大,且粒度分布宽,以及通过气流粉碎降低粒度存在严重安全风险,导致无法在合成过程中直接获得粒度可控、分布窄的超细产物问题,而提供一种超细硝酸脒基脲铜及其合成方法和在汽车安全气囊气体发生剂中的应用
[0046]1、本发明提供的一种超细硝酸脒基脲铜的合成方法,采用反相微乳液法将硝酸铜水相和双氰胺水相分别负载于独立的微乳液体系中,通过在微乳液混合过程中控制微液滴尺寸,实现了产物粒径在合成过程中的直接调控,产物D50粒径可控制在3~30μm范围内,避免了传统气流粉碎等高能后处理工序带来的安全风险,从根本上解决了含能材料粉碎过程中的安全隐患问题。
Smart Images

Figure FT_1 
Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to energetic materials for automotive airbag gas generators, specifically to an ultrafine copper amidine nitrate, its synthesis method, and its application in automotive airbag gas generators. Background Technology
[0002] As a key device for passive safety protection of occupants, automotive airbags rely heavily on a gas generator as one of their core components. The performance of this gas generator largely depends on the properties of the gas generating agent material. Traditional gas generating agents primarily use sodium azide as the gas-generating component. While this composition typically produces nitrogen gas upon ignition, meeting industry standards, sodium azide is highly toxic and explosive. Furthermore, it readily forms sensitive azides upon contact with heavy metals (such as copper and lead), posing potential risks in the safe handling, supply, and disposal of energetic materials. Therefore, developing non-azide gas generating agent materials has become an important research direction in this field.
[0003] In the research of non-azide gas generators, the binary system composed of guanidine nitrate (GN) and basic copper nitrate (BCN) has attracted widespread attention due to its good combustion temperature matching and high gas generation efficiency. However, in practical applications, this system still suffers from problems such as insufficient combustion rate and high combustion temperature, which restricts its further application in high-performance automotive airbags.
[0004] To improve the performance of the guanidine nitrate-basic copper nitrate gas generator system, US Patent 6602365B1, "GASGENERATION VIA METAL COMPLEXES OF GUANYLUREA NITRATE," proposed a novel gas generator material—a metal complex of amidourea nitrate. This patent discloses the synthesis method of copper amidourea nitrate complex (CuGUN) and its application effects in gas generators. CuGUN can be prepared by reacting amidourea nitrate with a complexing agent containing a transition metal element (such as basic copper carbonate) in an aqueous slurry under elevated temperature conditions.
[0005] US Patent 6602365B1 also systematically studied the effect of different amounts of CuGUN replacing guanidine nitrate on the performance of gas generator formulations. The results showed that the burning rate gradually increased with increasing amounts of CuGUN partially replacing guanidine nitrate (up to 4 mm / s), while the burning temperature gradually decreased with increasing CuGUN substitution (up to 245°C). The addition of CuGUN lowered the burning temperature of the gas generator formulation, directly leading to higher levels of nitrogen oxides (NOx) in the generated gaseous products.x The content of guanidine nitrate is reduced; at the same time, the density of the gas generator formulation increases after CuGUN partially replaces guanidine nitrate. Although the mass gas production is reduced significantly, the volumetric gas production changes very little. Therefore, CuGUN, as a novel gas generator component, has significant advantages in improving combustion rate, reducing combustion temperature, and decreasing harmful gas emissions.
[0006] Regarding the industrial preparation of CuGUN, Chinese patent CN109836358B discloses a method for preparing copper salt complex of amidine nitrate. This method uses dicyandiamide as a raw material, preparing a solution by mixing dicyandiamide and solvent at a mass percentage ratio of 10%~20%:90%~80% and heating until transparent. Then, copper nitrate, at a mass ratio of 1.4~1.5 times that of dicyandiamide, is added over 30 minutes~1 hour at 50℃~70℃. The mixture is then heated to 80℃~95℃ and reacted for another 2~5 hours. Finally, the product is cooled to precipitate, filtered, washed, and dried to obtain the CuGUN product. This method uses excess copper nitrate with water of crystallization as a reactant, which can be completely removed in the subsequent washing process. The synthesized CuGUN has high purity, a short reaction cycle, is environmentally friendly, easy to operate, and has low production costs, making it particularly suitable for large-scale production.
[0007] However, the CuGUN product synthesized according to the method in CN109836358B has the following obvious defects in practical use:
[0008] First, the product has a relatively large particle size and wide distribution. The CuGUN directly synthesized by this method has a particle size D50 (the particle size value corresponding to 50% of the cumulative number or volume of particles in the sample) in the range of 30~50μm, which is relatively large and has a wide range. Although the addition of CuGUN with this particle size to the guanidine nitrate-basic copper nitrate system can improve the burning rate and burning temperature, due to its large particle size and limited specific surface area, a high addition amount is required to achieve ideal combustion performance. However, excessive addition will lead to a significant reduction in volumetric gas production and mass gas production, creating a performance contradiction.
[0009] Second, physical pulverization methods pose safety risks. To overcome the problem of excessively large particle size, existing technologies attempt to grind and pulverize synthesized CuGUN with a D50 of 30-50 μm using air jet milling, aiming to reduce the particle size to a D50 of 3-6 μm. However, CuGUN is an energetic material, and the high-energy processing of air jet milling presents significant safety risks such as combustion and explosion, greatly limiting the industrial feasibility of this post-processing approach.
[0010] In summary, existing CuGUN preparation technologies face a dilemma: on the one hand, directly synthesized products have excessively large particle sizes, affecting their addition efficiency and overall performance in gas generator formulations; on the other hand, reducing particle size through physical pulverization poses serious safety risks. Therefore, how to effectively control the particle size of CuGUN directly during the synthesis process, especially to obtain ultrafine products with small particle size (D50≤6μm) and narrow particle size distribution, has become a pressing technical challenge in this field. Summary of the Invention
[0011] The purpose of this invention is to solve the problems of existing copper nitrate products having large particle size and wide particle size distribution, and the serious safety risks associated with reducing particle size through air jet milling, which makes it impossible to directly obtain ultrafine products with controllable particle size and narrow distribution during the synthesis process. The invention provides an ultrafine copper nitrate, its synthesis method, and its application in automotive airbag gas generators.
[0012] The inventive concept of this invention is to use a reverse microemulsion method, in which copper nitrate aqueous phase and dicyandiamide aqueous phase are respectively loaded into a reverse microemulsion system to carry out coordination reaction and hydrolysis reaction, and by controlling key process parameters such as water-oil ratio, stirring speed and dropping rate, the particle size of the product can be controllably adjusted in the range of 3~30μm, and in particular, ultrafine products with D50 of 3~6μm can be directly obtained.
[0013] To achieve the above objectives and complete the above inventive concept, the technical solution provided by this invention is as follows:
[0014] A method for synthesizing ultrafine amidourea copper nitrate, characterized by the following steps:
[0015] Step 1: Dissolve copper nitrate trihydrate in deionized water, add dispersant, and stir at 60~70℃ to obtain aqueous phase A of copper nitrate;
[0016] Dicyandiamide was dissolved in deionized water and dissolved with ultrasonic assistance at 60-70℃. After filtration to remove impurities, dicyandiamide aqueous phase B was obtained.
[0017] Step 2: Mix isoparaffin solvent oil, Span80 and Tween80, and stir at 60℃~70℃ until transparent and homogeneous to form an oil phase-surfactant system; add the dicyandiamide aqueous phase B to the system, stir to form a dicyandiamide-loaded reverse microemulsion M2, and keep it at 60℃~70℃ for later use.
[0018] Separately, take isoparaffin solvent oil, Span80 and Tween80 and mix them. Stir at 60℃~70℃ until transparent and homogeneous to form an oil phase-surfactant system. Add the copper nitrate aqueous phase A to the system and stir to form a copper nitrate-loaded reverse microemulsion M1. Keep it at 60℃~70℃ for later use.
[0019] Step 3: Place the reverse microemulsion M2 in a constant temperature water bath at 60~70℃, and add the reverse microemulsion M1 dropwise to the reverse microemulsion M2 under stirring to carry out the coordination reaction. After the addition is complete, the reaction system is obtained. Continue to keep the reaction system warm and stir for 30min~60min.
[0020] Step 4: Heat the reaction system to 90℃~95℃, and then keep it at this temperature to carry out the hydrolysis reaction;
[0021] Step 5: After the hydrolysis reaction is completed, cool down, add anhydrous ethanol to the reaction system to break the emulsion, separate by centrifugation, and then filter to obtain the first filter cake. Wash the first filter cake to obtain the second filter cake.
[0022] Step 6: Vacuum dry the second filter cake to obtain the ultrafine copper nitrate amidine urea product.
[0023] Further, in step 1, the mass ratio of copper nitrate trihydrate to deionized water is 1.00 g: 1.00~2.40 mL; the dispersant is PEG-400, or a combination of PEG-400 and PVP-K30, and the amount of dispersant is 2.5%~14.0% of the mass of copper nitrate trihydrate; the mass ratio of dicyandiamide to deionized water is 1.00 g: 6.35~12.80 mL;
[0024] In step 2, the isoparaffin solvent oil is IsoparG; the volume ratio of IsoparG, Span80, Tween80, and dicyandiamide aqueous phase B in the reverse microemulsion M2 is 130.00~135.00mL: 2.80~3.20g: 1.00g: 9.50~16.00mL;
[0025] The volume ratio of IsoparG, Span80, Tween80, and copper nitrate aqueous phase A in the reverse microemulsion M1 is 130.00~135.00mL: 2.80~3.20g: 1.00g: 13.00~14.50mL.
[0026] Further, in step 5, the washing of the first filter cake specifically involves sequentially washing the first filter cake with anhydrous ethanol, anhydrous isopropanol, and deionized water in a gradient manner.
[0027] Furthermore, in step 3, the stirring speed of the coordination reaction is 400 rpm to 700 rpm, and the dropping rate of the reverse microemulsion M1 is 0.2 mL / min to 0.5 mL / min;
[0028] In step 4, the heating rate is 6℃ / h ~ 10℃ / h, the hydrolysis reaction temperature is 92℃, and the holding time is 5h ~ 7h;
[0029] In step 5, when demulsifying, the amount of anhydrous ethanol added is 8% to 12% of the total volume of the reaction system, the stirring speed during demulsification is 200 rpm to 300 rpm, and the duration is 15 min to 25 min; the centrifugation speed is 6000 rpm to 8000 rpm, and the duration is 10 min to 15 min.
[0030] In step 6, the vacuum drying temperature is 60℃~70℃, the vacuum degree is 0.08 MPa~0.09 MPa, and the drying time is 6h~10h.
[0031] Further, in step 5, the gradient washing specifically involves:
[0032] Step 5a: Wash with anhydrous ethanol 2-4 times, then filter to remove anhydrous ethanol;
[0033] Step 5b: Wash 2-3 times with anhydrous isopropanol, then filter to remove the anhydrous isopropanol;
[0034] Step 5c: Rinse once with deionized water, and then perform vacuum filtration to obtain a second filter cake, wherein the moisture content of the second filter cake is ≤5%.
[0035] Furthermore, in steps 2 and 3, by controlling the following parameter combinations, step 6 obtains ultrafine copper nitrate products with different particle size ranges:
[0036] Step 2 controls the water-oil ratio of reverse microemulsion M1 to be 0.100 and the water-oil ratio of reverse microemulsion M2 to be 0.071~0.072. Simultaneously, Step 3 controls the stirring speed of the coordination reaction to be 700 rpm and the dropping acceleration rate of reverse microemulsion M1 to be 0.5 mL / min. Step 6 obtains an ultrafine copper nitrate product with a D50 of 3~6 μm.
[0037] Step 2 controls the water-oil ratio of reverse microemulsion M1 to be 0.100 and the water-oil ratio of reverse microemulsion M2 to be 0.095~0.096. Meanwhile, in step 3, the stirring speed of the coordination reaction is controlled at 500 rpm and the dropping rate of reverse microemulsion M1 is controlled at 0.3 mL / min. In step 6, an ultrafine copper nitrate product with a D50 of 10~20 μm is obtained.
[0038] Step 2 controls the water-oil ratio of reverse microemulsion M1 to be 0.100 and the water-oil ratio of reverse microemulsion M2 to be 0.119~0.121. Simultaneously, Step 3 controls the stirring speed of the coordination reaction to be 400 rpm and the dropping acceleration rate of reverse microemulsion M1 to be 0.2 mL / min. Step 6 obtains an ultrafine copper nitrate product with a D50 of 20~30 μm.
[0039] The water-oil ratio is the volume ratio of water to isoparaffin solvent oil in reverse microemulsion M1 or reverse microemulsion M2. The water-oil ratio is controlled by changing the amount of deionized water added in step 1 and the amount of isoparaffin solvent oil added in step 2.
[0040] Meanwhile, the present invention also provides an ultrafine amidourea copper nitrate, which is special in that it is prepared by the above-mentioned synthesis method of ultrafine amidourea copper nitrate.
[0041] Furthermore, the D50 particle size of the ultrafine copper amidocyanate is 3~30μm, the particle size distribution PDI≤0.35, and the particle morphology is irregular particles.
[0042] Furthermore, the present invention also provides an application of the above-mentioned ultrafine copper nitrate amidourea in automotive airbag gas generators.
[0043] Furthermore, the application method of ultrafine amidine urea copper nitrate in automotive airbag gas generators is as follows:
[0044] The ultrafine copper amidocyanate nitrate is mixed with guanidine nitrate, basic copper nitrate, α-Al2O3, and magnesium stearate, and then compressed into tablets to obtain a tablet for use in automotive airbag gas generators. In the tablet for automotive airbag gas generators, the mass fraction of ultrafine copper amidocyanate nitrate is 10%, the mass fraction of guanidine nitrate is 42.07%, the mass fraction of basic copper nitrate is 44.93%, the mass fraction of α-Al2O3 is 3%, and the amount of magnesium stearate added is 0.2% of the total mass of the main formulation of ultrafine copper amidocyanate nitrate nitrate, guanidine nitrate, basic copper nitrate, and α-Al2O3.
[0045] Compared with the prior art, the present invention has the following beneficial technical effects:
[0046] 1. The present invention provides a method for synthesizing ultrafine copper amidine urea nitrate. The method employs a reverse microemulsion method to load the aqueous phases of copper nitrate and dicyandiamide into independent microemulsion systems. By controlling the microdroplet size during the microemulsion mixing process, the particle size of the product can be directly controlled during the synthesis process. The D50 particle size of the product can be controlled within the range of 3~30μm, avoiding the safety risks brought about by traditional high-energy post-processing steps such as air jet milling, and fundamentally solving the safety hazards in the process of pulverizing energetic materials.
[0047] 2. The present invention provides a method for synthesizing ultrafine copper amidine nitrate. By synergistically controlling key parameters such as water-oil ratio, stirring speed, and dropping rate, it can flexibly produce products with various particle sizes such as D50 of 3~6μm, 10~20μm, and 20~30μm, and the product has a narrow particle size distribution (PDI≤0.35), which meets the differentiated requirements of different gas generator formulations for copper amidine nitrate particle size.
[0048] 3. The present invention provides a method for synthesizing ultrafine copper nitrate amidine urea. The synthesized ultrafine product (D50=3~6μm) only needs to be added to the gas generator formulation at 10% to achieve a significant increase in combustion rate and a substantial decrease in combustion temperature, while maintaining the same volumetric gas production and mass gas production. Its comprehensive performance is significantly better than that of the prior art.
[0049] 4. The present invention provides a method for synthesizing ultrafine amidine urea copper nitrate, which is simple to operate, has mild reaction conditions, and low production cost. Each step can be achieved using conventional chemical equipment without the need for special equipment, making it suitable for industrial-scale production.
[0050] 5. The present invention provides an ultrafine copper amidocyanate nitrate with a D50 particle size that can be controlled within the range of 3~30μm and a narrow particle size distribution (PDI≤0.35), which can meet the differentiated requirements of different automotive airbag gas generator formulations for copper amidocyanate nitrate particle size.
[0051] 6. The application of ultrafine amidourea copper nitrate in automotive airbag gas generators provided by this invention allows for the addition of only 10% of ultrafine amidourea copper nitrate to the automotive airbag gas generator formulation, which can significantly improve the combustion rate and greatly reduce the combustion temperature, while maintaining the same volumetric gas production and mass gas production. Its overall performance is significantly better than that of existing automotive airbag gas generators. Attached Figure Description
[0052] Figure 1 This is a flowchart illustrating an embodiment of a method for synthesizing ultrafine amidourea copper nitrate according to the present invention. Detailed Implementation
[0053] To make the objectives, advantages, and features of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings and three specific embodiments. Those skilled in the art should understand that these embodiments are merely used to explain the technical principles of the present invention and are not intended to limit the scope of protection of the present invention.
[0054] Example 1
[0055] This example describes the preparation of ultrafine copper amidine nitrate with a D50 of 3-6 μm.
[0056] A method for synthesizing ultrafine amidine urea copper nitrate with a D50 of 3-6 μm is shown in the flowchart. Figure 1 This includes the following steps:
[0057] Step 1: Raw material pretreatment and aqueous phase preparation
[0058] Step 1.1: Preparation of copper nitrate aqueous phase A: Take a 100mL beaker, add 10mL of deionized water, place it in a 65℃ constant temperature water bath, then add 10.0g of copper nitrate trihydrate and 0.25g of PEG-400 (Polyethyleneglycol-400), and stir (in the three embodiments of this application, the stirring method is magnetic stirrer), at a stirring speed of 300rpm, and continue stirring to dissolve for 15min until the solution becomes a clear blue liquid (with no undissolved particles), and keep it at 65℃ for later use. PEG-400, as a co-solvent, can adsorb onto the surface of tiny particles in the copper nitrate solution or the crystal nuclei generated in subsequent reactions, effectively preventing particle aggregation through steric hindrance, ensuring that the reactants in the aqueous phase are highly dispersed, laying the foundation for the subsequent formation of products with uniform particle size. PEG-400 has a certain degree of hydrophilicity, which can fine-tune the polarity and viscosity of the aqueous phase, affecting the curvature and size of droplets when preparing reverse microemulsions, thus indirectly affecting the particle size control of the final product.
[0059] Step 1.2: Preparation of dicyandiamide aqueous phase B: Take a 250mL beaker, add 40mL of deionized water, place it in a 65℃ constant temperature water bath, then add 6.3g of dicyandiamide, place it in an ultrasonic cleaner for 20min of ultrasonic-assisted dissolution, while stirring at 200rpm until the solution is clear. Remove any small amount of precipitate by filtration with a 0.45μm filter membrane, and keep it at 65℃ for later use.
[0060] Step 2: Preparation of two reverse microemulsions
[0061] Step 2.1: Preparation of reverse microemulsion M2: Add 556 mL of isoparaffin solvent oil Isopar G to a 1 L three-necked flask, place a magnetic stir bar in the flask, and put it in a 65℃ constant temperature water bath. Start stirring at 500 rpm. Add 12.5 g of Span 80 and 4.2 g of Tween 80 sequentially, and continue stirring for 30 min until the solution is clear and homogeneous. Add 40 mL of dicyandiamide aqueous phase B to the above solution at a rate of 1 mL / min, adjust the stirring speed to 600 rpm, and continue stirring for 20 min to form a transparent reverse microemulsion M2. Keep it at 65℃ for later use. The water-to-oil ratio of the reverse microemulsion M2 prepared in this step is 40 mL / 556 mL ≈ 0.072. The water-to-oil ratio refers to the volume ratio of water to isoparaffin solvent oil in either reverse microemulsion M1 or reverse microemulsion M2, and the same applies below. An increased water-to-oil ratio (W / O) leads to larger droplet volumes; a decreased stirring speed weakens dispersion strength, making particles easier to grow; a slower droplet acceleration rate results in more uniform local concentration and more sufficient particle growth; the amount of dispersant can be adjusted as needed (the larger the particle size, the more dispersant can be used). It should be noted that in practical applications, isoalkane solvents such as Isopar H, C11 isoalkane solvents, or Shell TD type oils (such as Shellsol TD), as well as other types like n-octane and n-heptane, can also be used. In this example, Isopar G is used as the oil phase, with the following physicochemical parameters: distillation range 167~176℃, flash point 44℃, and density 0.748 g / cm³. 3 The viscosity (25℃) is 1.49 mm² / s, the aromatic content is <0.005%, the surface tension (25℃) is 23 mN / m, and the refractive index (20℃) is 1.418. Isopar G was chosen because of its good solubility in the Span80 and Tween80 compound surfactant system, enabling it to form a stable oil-water interface film over a wide range of proportions. This facilitates the formation of a uniform and transparent reverse microemulsion and avoids participating in side reactions or introducing harmful impurities, ensuring product purity. In this step, the compounding of Span80 (lipophilic) and Tween80 (hydrophilic) forms a dense mixed adsorption film at the oil-water interface, significantly reducing interfacial tension and preventing microdroplet aggregation. This ensures the stability of the reverse microemulsion system during preparation at 65℃ and hydrolysis at 92℃. Meanwhile, the orderly arrangement of the two at the oil-water interface determines the radius of curvature and size distribution of the microdroplets, providing a structural basis for the control of the particle size of the subsequent products; the interfacial film of Span80 / Tween80 is temperature sensitive and is easily destroyed after the addition of anhydrous ethanol, which is beneficial for the separation of the product from the microemulsion system and simplifies the post-processing steps.
[0062] Step 2.2: Preparation of reverse microemulsion M1: Take a 500mL three-necked flask, add 100mL of IsoparG, 2.2g of Span80, and 0.7g of Tween80, stir to dissolve, then add 10mL of copper nitrate aqueous phase A, stir for 20min to form a blue transparent microemulsion M1, and keep it at 65℃ for later use. The water-to-oil ratio of the reverse microemulsion M1 prepared in this step is 10mL / 100mL = 0.100.
[0063] Step 3: Microemulsion mixing and coordination reaction
[0064] A 1L three-necked flask loaded with reverse microemulsion M2 was placed in a 65℃ constant-temperature water bath. A constant-pressure dropping funnel was installed, and reverse microemulsion M1 was transferred into the dropping funnel. While maintaining a stirring speed of 700 rpm, reverse microemulsion M1 was added dropwise to reverse microemulsion M2 at a rate of 0.5 mL / min. The addition was completed after approximately 20 minutes, with the temperature maintained at 65℃ during the addition. The reaction system solution was observed to gradually transform into a light blue suspension. After the addition was complete, stirring was continued for another 30 minutes to ensure uniform mixing of the microemulsions and prevent localized agglomeration. This step utilizes the confined space effect of microdroplets as "nanoreactors" by slowly adding copper nitrate-loaded reverse microemulsion M1 to dicyandiamide-loaded reverse microemulsion M2, allowing the coordination reaction to proceed controllably within the droplets, achieving preliminary shaping and uniform distribution of the product particle size.
[0065] Step 4: Heating and hydrolysis reaction:
[0066] The water bath temperature was raised to 90℃ at a rate of 10℃ / h (approximately 2.5h to reach 90℃); this temperature was then maintained at 92±1℃ for 5h with stirring at 400 rpm; after the holding period, the water bath heating was turned off, and the solution was allowed to cool to below 40℃ (approximately 1-1.5h to reach this target). This step, by raising the temperature to 90℃ and holding it for 5h, allows the precursor to undergo a hydrolysis reaction in the microemulsion system, converting the coordination product into the final ultrafine copper nitrate amidine urea crystals, thus achieving the stabilization and shaping of the product structure.
[0067] Step 5: Demulsification, separation, and gradient washing:
[0068] Step 5.1, Demulsification: Add a total of 100 mL of anhydrous ethanol to the reaction system at a dropping rate of 2 mL / min, while stirring at 300 rpm for 15 min to allow the reaction system to separate into layers. This step involves adding anhydrous ethanol to disrupt the oil-water interface film, causing the originally stable reverse microemulsion system to become unstable and separate into layers, thus achieving the initial separation of the oil phase and the aqueous phase (including the product).
[0069] Step 5.2, Separation: Transfer the reaction system to 50mL centrifuge tubes (total number of centrifuge tubes: 10 tubes), centrifuge at 8000rpm for 10min, discard the supernatant, and filter using a 0.45μm filter membrane to obtain a primary filter cake with a water content ≤30%. After combining the precipitates, continue filtration using a small vacuum filtration device (using a 0.45μm filter membrane) to remove residual supernatant, obtaining a first filter cake with a water content ≤30%. This step separates the product from the liquid phase system through centrifugation and vacuum filtration, using centrifugal force and negative pressure to obtain a primary filter cake with a water content ≤30%, creating conditions for subsequent washing and drying.
[0070] Step 5.3, Gradient Washing:
[0071] a. First, perform a primary washing (the purpose is to remove surfactants): Wash the first filter cake four times with 20 mL of anhydrous ethanol, then remove the anhydrous ethanol by vacuum filtration to obtain the first filter cake after the first washing.
[0072] b. Next, a second washing process is performed (the purpose of which is to remove residual organic matter): the first filter cake after the first washing is washed three times with 5 mL of anhydrous isopropanol, and then the anhydrous isopropanol is removed by suction filtration to obtain the first filter cake after the second washing.
[0073] c. Finally, rinse with water (to remove free nitrate): Quickly rinse the first filter cake after the second washing with 5 mL of deionized water, and the second filter cake obtained after filtration has a moisture content of ≤5%.
[0074] Step 6, Drying and Finished Product Inspection:
[0075] The second filter cake was transferred to a petri dish, with a spreading thickness ≤2 mm. It was then dried in a vacuum drying oven at 70℃ and 0.08 MPa for 6 hours until the moisture content of the second filter cake was ≤0.5%. The dried product was a light blue, loose powder, which was gently ground in an agate mortar to obtain the ultrafine copper nitrate amidine urea. Gentle grinding was used to avoid over-grinding, which would affect the particle size.
[0076] The D50 of the ultrafine copper nitrate amidourea product in this embodiment was 4.74 μm, as determined by a laser particle size analyzer. ICP analysis showed a Cu content of 16.183%, and SEM (Scanning Electron Microscope) observation revealed its morphology to be irregular particles.
[0077] Meanwhile, this embodiment also provides an ultrafine copper nitrate amidine urea, which is prepared by the above method. Its D50 particle size is 3~6μm, the particle size distribution PDI≤0.35, and the particle morphology is irregular particles.
[0078] Furthermore, this embodiment also provides the application of ultrafine amidourea copper nitrate in automotive airbag gas generators. Specifically, the ultrafine amidourea copper nitrate is mixed with guanidine nitrate, basic copper nitrate, α-Al2O3, and magnesium stearate, and then compressed into tablets to obtain tablets for use in automotive airbag gas generators. In the tablets used in automotive airbag gas generators, the mass fraction of ultrafine amidourea copper nitrate is 10%, the mass fraction of guanidine nitrate is 42.07%, the mass fraction of basic copper nitrate is 44.93%, the mass fraction of α-Al2O3 is 3%, and the amount of magnesium stearate added is 0.2% of the total mass of the main formulation of ultrafine amidourea copper nitrate, guanidine nitrate, basic copper nitrate, and α-Al2O3.
[0079] Example 2
[0080] This embodiment describes the preparation of ultrafine copper amidine nitrate with a D50 of 10~20μm.
[0081] A method for synthesizing ultrafine copper amidine nitrate with a D50 of 10-20 μm is shown in the flowchart. Figure 1 This includes the following steps:
[0082] Step 1: Raw material pretreatment and aqueous phase preparation
[0083] Step 1.1: Preparation of copper nitrate aqueous phase A: Take a 250mL beaker, add 16mL of deionized water, place it in a 65℃ constant temperature water bath, and then add 10.0g of copper nitrate trihydrate, 0.64g of PEG-400 and 0.1g of PVP-K30. Stir at 250rpm for 20min until the solution turns into a clear blue liquid (with no undissolved particles). Keep it at 65℃ for later use.
[0084] Step 1.2: Preparation of dicyandiamide aqueous phase B: Take a 500mL beaker, add 64mL of deionized water, place it in a 65℃ constant temperature water bath, then add 6.8g of dicyandiamide, and place it in an ultrasonic cleaner (the ultrasonic cleaner in this embodiment has a power of 60W) for 25min of ultrasonic-assisted dissolution, while stirring at a speed of 180rpm until the solution is transparent. Filter out any small amount of precipitate to remove impurities, and keep it at 65℃ for later use.
[0085] Step 2: Preparation of two reverse microemulsions
[0086] Step 2.1: Preparation of reverse microemulsion M2: Add 667 mL of isoparaffin solvent oil Isopar G to a 1 L three-necked flask, place a magnetic stir bar in the flask, and put it in a 65 °C water bath. Start stirring at 400 rpm. Add 15.0 g of Span 80 and 5.0 g of Tween 80 sequentially, and continue stirring for 40 min until the solution is clear and homogeneous (judgment criteria: turbidity ≤ 8 NTU, no visible layering, and no turbidity). Inject 64 mL of dicyandiamide aqueous phase B into the above solution at a rate of 0.8 mL / min, adjust the stirring speed to 500 rpm, and continue stirring for 30 min to form a transparent reverse microemulsion M2. Keep it at 65 °C for later use. The water-to-oil ratio of the reverse microemulsion M2 prepared in this step is 64 mL / 667 mL ≈ 0.096.
[0087] Step 2.2: Preparation of reverse microemulsion M1: Take a 500mL three-necked flask, add 160mL of Isopar G, 3.5g of Span 80, and 1.2g of Tween 80, stir to dissolve, then add 16mL of copper nitrate aqueous phase A, stir for 30min to form a blue transparent microemulsion M1, and keep it at 65℃ for later use. The water-to-oil ratio of the reverse microemulsion M1 prepared in this step is 10mL / 100mL = 0.100.
[0088] Step 3: Microemulsion mixing and coordination reaction
[0089] A 1L three-necked flask loaded with reverse microemulsion M2 was placed in a 65℃ constant temperature water bath. A constant pressure dropping funnel was installed, and reverse microemulsion M1 was transferred into the dropping funnel. While maintaining a stirring speed of 500 rpm, reverse microemulsion M1 was added dropwise to reverse microemulsion M2 at a rate of 0.3 mL / min. The addition was completed after about 53 min. During the addition, the temperature was maintained at 65℃. It was observed that the reaction system solution gradually turned into a light blue suspension. After the addition was completed, the mixture was kept at the temperature and stirred for another 40 min to ensure that the microemulsion was uniformly mixed and free from local agglomeration.
[0090] Step 4: Heating and hydrolysis reaction
[0091] The water bath temperature was raised to 90℃ at a rate of 8℃ / h (approximately 3.1h to 90℃); the temperature was then maintained at 92±1℃ for 6h while stirring at a speed of 350rpm; after the holding period, the water bath heating was turned off, and the solution was allowed to cool to below 40℃ (approximately 1~1.5h to reach this target).
[0092] Step 5: Demulsification, separation, and gradient washing
[0093] Step 5.1, Demulsification: Add a total of 160 mL of anhydrous ethanol to the reaction system at a dropping rate of 1.5 mL / min, while stirring at 250 rpm for 20 min to allow the reaction system to separate into layers;
[0094] Step 5.2, Separation: Transfer the reaction system to 50mL centrifuge tubes (total number of centrifuge tubes is 13), centrifuge at 7000rpm for 12min, then discard the supernatant, filter using a 0.45μm filter membrane to obtain a primary filter cake with a water content ≤35%; after the precipitates are combined, continue to filter using a small vacuum filtration device (using a 0.45μm filter membrane) to remove the residual supernatant, and obtain the first filter cake with a water content ≤30%.
[0095] Step 5.3, Gradient Washing:
[0096] a. First, perform a primary washing (the purpose is to remove surfactants): wash the first filter cake four times with 32 mL of anhydrous ethanol, then remove the anhydrous ethanol by vacuum filtration to obtain the first filter cake after the first washing.
[0097] b. Next, a second washing process is performed (the purpose of which is to remove residual organic matter): the first filter cake after the first washing is washed three times with 8 mL of anhydrous isopropanol, and then the anhydrous isopropanol is removed by suction filtration to obtain the first filter cake after the second washing.
[0098] c. Finally, rinse with water (to remove free nitrate): Quickly rinse the first filter cake after the second washing with 8 mL of deionized water, and the second filter cake obtained after filtration has a moisture content of ≤5%.
[0099] Step 6: Drying and Finished Product Inspection
[0100] The second filter cake was transferred to a petri dish, with a spreading thickness ≤3mm. It was then dried in a vacuum drying oven at 65℃ and 0.08MPa for 8 hours until the moisture content of the second filter cake was ≤0.8%. The dried product was a light blue, loose powder, which was gently ground in an agate mortar to obtain the ultrafine copper amidine nitrate nitrate product.
[0101] The ultrafine copper nitrate nitrate product of this embodiment has a D50 of 16.85 μm and a Cu content of 16.205%. SEM observation shows that its morphology consists of irregular particles.
[0102] Meanwhile, this embodiment also provides an ultrafine copper nitrate amidine urea, which is prepared by the above method. Its D50 particle size is 10~20μm, the particle size distribution PDI≤0.35, and the particle morphology is irregular particles.
[0103] Furthermore, this embodiment also provides the application of ultrafine amidourea copper nitrate in automotive airbag gas generators. Specifically, the ultrafine amidourea copper nitrate is mixed with guanidine nitrate, basic copper nitrate, α-Al2O3, and magnesium stearate, and then compressed into tablets to obtain tablets for use in automotive airbag gas generators. In the tablets used in automotive airbag gas generators, the mass fraction of ultrafine amidourea copper nitrate is 10%, the mass fraction of guanidine nitrate is 42.07%, the mass fraction of basic copper nitrate is 44.93%, the mass fraction of α-Al2O3 is 3%, and the amount of magnesium stearate added is 0.2% of the total mass of the main formulation of ultrafine amidourea copper nitrate, guanidine nitrate, basic copper nitrate, and α-Al2O3.
[0104] Example 3
[0105] This embodiment describes the preparation of ultrafine copper amidine nitrate with a D50 of 20-30 μm.
[0106] A method for synthesizing ultrafine copper amidine nitrate with a D50 of 20-30 μm is shown in the flowchart. Figure 1 This includes the following steps:
[0107] Step 1: Raw material pretreatment and aqueous phase preparation
[0108] Step 1.1: Preparation of copper nitrate aqueous phase A: Take a 500mL beaker, add 24mL of deionized water, place it in a 65℃ constant temperature water bath, then add 10.0g of copper nitrate trihydrate, 1.2g of PEG-400 and 0.2g of PVP-K30, stir at 200rpm, and continue stirring for 25min until the solution turns into a clear blue liquid. Keep it at 65℃ for later use.
[0109] Step 1.2: Preparation of dicyandiamide aqueous phase B: Take a 500mL beaker, add 96mL of deionized water, place it in a 65℃ constant temperature water bath, then add 7.5g of dicyandiamide, place it in an ultrasonic cleaner for 30min of ultrasonic-assisted dissolution, stirring at 150rpm, filter to remove impurities until the solution is clear, filter to remove any small amount of precipitate, and keep it at 65℃ for later use.
[0110] Step 2: Preparation of two reverse microemulsions
[0111] Step 2.1: Preparation of reverse microemulsion M2: Add 800 mL of isoparaffin solvent oil Isopar G to a 1 L three-necked flask, place a magnetic stir bar in the flask, and put it in a 65 °C water bath. Start stirring at 350 rpm. Add 18.0 g of Span 80 and 6.0 g of Tween 80 sequentially, and continue stirring for 50 min until the solution is clear and homogeneous. Add 96 mL of dicyandiamide aqueous phase B to the above solution at a rate of 0.5 mL / min, adjust the stirring speed to 400 rpm, and continue stirring for 40 min to form a transparent reverse microemulsion M2. Keep it at 65 °C for later use. The water-to-oil ratio of the reverse microemulsion M2 prepared in this step is 96 mL / 800 mL = 0.120.
[0112] Step 2.2: Preparation of reverse microemulsion M1: Take a 500mL three-necked flask, add 240mL of Isopar G, 5.3g of Span 80, and 1.8g of Tween 80, stir to dissolve, then add 24mL of copper nitrate aqueous phase A, stir for 40min to form a blue transparent microemulsion M1, and keep it at 65℃ for later use. The water-to-oil ratio of the reverse microemulsion M1 prepared in this step is 10mL / 100mL = 0.100.
[0113] Step 3: Microemulsion mixing and coordination reaction
[0114] A 1L three-necked flask loaded with reverse microemulsion M2 was placed in a 65℃ constant temperature water bath. A constant pressure dropping funnel was installed, and reverse microemulsion M1 was transferred into the dropping funnel. The stirring speed was kept at 400 rpm, and reverse microemulsion M1 was added dropwise to reverse microemulsion M2 at a rate of 0.2 mL / min. The addition was completed after about 120 min. The temperature was kept at 65℃ during the addition. The reaction system solution was observed to gradually turn into a light blue suspension. After the addition was completed, the mixture was kept at the temperature and stirred for another 60 min to ensure that the microemulsion was uniformly mixed and free from local agglomeration.
[0115] Step 4: Heating and hydrolysis reaction
[0116] The water bath temperature is raised to 90℃ at a rate of 6℃ / h (approximately 4.2h to 90℃); the temperature is then maintained at 92±1℃ for 7h while stirring at a speed of 300rpm; after the holding period, the water bath heating is turned off and the temperature is lowered to below 40℃ (approximately 1~1.5h to reach this target).
[0117] Step 5: Demulsification, separation, and gradient washing
[0118] Step 5.1, Demulsification: Add a total of 240 mL of anhydrous ethanol to the reaction system at a dropping rate of 1 mL / min, while stirring at 200 rpm for 25 min to allow the reaction system to separate into layers.
[0119] Step 5.2, Separation: Transfer the reaction system to 50mL centrifuge tubes (total number of centrifuge tubes is 19), centrifuge at 6000rpm for 15min, then discard the supernatant and perform vacuum filtration (using a 1.0μm filter membrane to avoid large particles clogging) to obtain a primary filter cake with a water content ≤40%; after the precipitates are combined, use a small vacuum filtration device (using a 0.45μm filter membrane) to remove the residual supernatant and obtain the first filter cake with a water content ≤30%.
[0120] Step 5.3, Gradient Washing:
[0121] a. First, perform a primary washing (the purpose is to remove surfactants): wash the first filter cake four times with 48 mL of anhydrous ethanol, then remove the anhydrous ethanol by vacuum filtration to obtain the first filter cake after the first washing.
[0122] b. Next, a second washing process is performed (the purpose of which is to remove residual organic matter): the first filter cake after the first washing is washed three times with 12 mL of anhydrous isopropanol, and then the anhydrous isopropanol is removed by suction filtration to obtain the first filter cake after the second washing.
[0123] c. Finally, rinse with water (to remove free nitrate): Quickly rinse the first filter cake after the second washing with 12 mL of deionized water, and the second filter cake obtained after filtration has a moisture content of ≤5%.
[0124] Step 6: Drying and Finished Product Inspection
[0125] The second filter cake was transferred to a petri dish, with a spreading thickness ≤4mm. It was then dried in a vacuum drying oven at 60℃ and 0.08MPa for 10 hours until the moisture content of the second filter cake was ≤1.0%. The dried product was a light blue, loose powder, which was gently ground in an agate mortar to obtain the ultrafine copper amidine nitrate nitrate product.
[0126] The ultrafine copper nitrate nitrate product of this embodiment has a D50 of 28.17 μm, a particle size distribution PDI ≤ 0.35, and a Cu content of 16.086%. SEM observation shows that its morphology consists of irregular particles.
[0127] Meanwhile, this embodiment also provides an ultrafine copper amidine nitrate, which is prepared by the above method. Its D50 particle size is 20~30μm, the particle size distribution PDI≤0.35, and the particle morphology is irregular particles.
[0128] Furthermore, this embodiment also provides the application of ultrafine amidourea copper nitrate in automotive airbag gas generators. Specifically, the ultrafine amidourea copper nitrate is mixed with guanidine nitrate, basic copper nitrate, α-Al2O3, and magnesium stearate, and then compressed into tablets to obtain tablets for use in automotive airbag gas generators. In the tablets used in automotive airbag gas generators, the mass fraction of ultrafine amidourea copper nitrate is 10%, the mass fraction of guanidine nitrate is 42.07%, the mass fraction of basic copper nitrate is 44.93%, the mass fraction of α-Al2O3 is 3%, and the amount of magnesium stearate added is 0.2% of the total mass of the main formulation of ultrafine amidourea copper nitrate, guanidine nitrate, basic copper nitrate, and α-Al2O3.
[0129] To verify the effect of different particle sizes of the products of this invention on the performance of the gas generator, gas generator tablets were prepared according to the test formulation in US Patent US6602365B1, using the contents disclosed in Examples 1 to 3 and Chinese Patent CN109836358B (i.e., copper nitrate product with D50 = 30~50μm), and their performance was tested. The methods are as follows:
[0130] Step α: Prepare tablet samples
[0131] Step α1: Using an electronic analytical balance, accurately weigh the following ingredients according to a single batch of 10g formula: 4.4930g basic copper nitrate, 4.2070g guanidine nitrate, 1.0000g copper amidocyanate nitrate (corresponding to Examples 1 to 3 and existing technology products, respectively), 0.3000g α-Al2O3, and 0.0200g magnesium stearate, with a weighing error ≤ ±0.0002g.
[0132] Step α2: Put basic copper nitrate, guanidine nitrate and copper nitrate of corresponding particle size into a V-type mixer and mix at a speed of 18 r / min for 30 min to obtain the first mixed powder.
[0133] Step α3: Add α-Al2O3 and magnesium stearate as a release agent to the first mixed powder, and continue mixing at 18 r / min for 30 min to obtain the second mixed powder; the mixing uniformity of the second mixed powder shall be in accordance with USP (United States Pharmacopeia). <1123> Standard testing: Five sampling points at different locations are randomly selected from the second mixed powder. The content of Cu and N elements is determined by HPLC (High Performance Liquid Chromatography). The coefficient of variation (CV) between each sampling point is calculated. A CV of ≤5% is required to pass the test. If the test is passed, proceed to step α4. If the test fails, steps α2 and / or α3 need to be repeated for mixing.
[0134] Step α4: Load the second mixed powder into the tableting mold; pre-coat the inner wall of the tableting mold with a small amount of magnesium stearate; set the tableting parameters as follows: tableting pressure: 18MPa, holding time: 10s, tableting speed: 15r / min; using the above parameters, compress the second mixed powder into multiple round tablet samples with a diameter of 15mm and a thickness of 4mm; visually inspect and remove tablet samples with appearance defects such as cracks, missing corners, and delamination to ensure that the tablet samples have an intact appearance and a smooth surface.
[0135] Step α5: Spread the tablets flat in a vacuum drying oven and dry them at 75℃ and a vacuum of -0.09MPa for 6 hours. After naturally cooling to room temperature, transfer them to a desiccator for storage (storage conditions: temperature 20~25℃, humidity ≤35%). Initial inspection: Randomly select 10 tablets with an average weight of 2.0000±0.0005g and a density of 1.85~1.95g / cm³.
[0136] Step α6: Perform multi-parameter synchronous testing using an integrated closed burster; calibrate the pressure sensor using a standard pressure source and the thermocouple using a tube furnace; select three tablets that passed the initial inspection, each weighing 2.0000±0.0005g.
[0137] Step α7, Initial Inspection
[0138] Quality inspection: Randomly select 10 tablet samples and weigh each tablet using an analytical balance; the average weight should be within the range of 2.0000±0.0005g, and the weight deviation of a single tablet should be ≤±0.02g.
[0139] Density testing: The density of the tablets is tested using the water displacement method. The target density is 1.85~1.95 g / cm³, and the relative standard deviation (RSD) is ≤2%. After both the quality test and the density test are qualified, proceed to step β. Otherwise, return to step α1 to prepare the tablet sample again.
[0140] Step β: Perform multi-parameter simultaneous testing on the tablet samples.
[0141] Step β1: Preparation before testing
[0142] Device calibration: Pressure sensors are calibrated at multiple points using a standard pressure source (calibration points cover 0~30MPa), and thermocouples are calibrated using a tube furnace within the range of 200~2000K. Recalibration is performed after every 10 tests.
[0143] Preparation of tablet samples: Randomly select 3 tablets from the tablets that pass the initial inspection, and the weight of each tablet is precisely controlled to be 2.0000±0.0005g.
[0144] Step β2, Sensor and Sample Installation
[0145] Burning rate test: Two through holes spaced 10mm apart are drilled along the axis of the tablet, and copper wire target wire (diameter ≤0.1mm) is inserted through them. The two ends of the target wire are connected to the data acquisition instrument to form a closed loop. When the tablet burns, the target wire melts and the burning rate is calculated based on the time interval of the target wire melting.
[0146] Combustion temperature test: Embed the K-type thermocouple probe into the center of the tablet and fix it with high-temperature resistant ceramic glue. Cover the thermocouple leads with a heat-insulating sleeve to prevent damage from high temperature.
[0147] Pressure test: The pressure sensor is installed on the inner wall of the burster, and the distance between the sensor probe and the sample surface is fixed at 5cm.
[0148] Step β3: Drug sample installation and sealing
[0149] Place the tablet with the sensor installed into the crucible inside the burster, ensuring the sample is centered. After sealing the burster, purge the air in the chamber with high-purity N2, finally adjusting the initial pressure to 0.1 MPa. Place the entire burster in a constant-temperature water bath, maintaining the temperature at 25℃ ± 0.5℃.
[0150] Step β4: Connect the gas production test linkage device
[0151] Connect the outlet of the generator to an inverted gas collecting bottle (pre-filled with water and inverted in a water tank) via a control valve. Place the gas collecting bottle in a 25°C constant temperature water bath. Before testing, confirm that the pipeline is airtight and leak-free.
[0152] Step β5, Data Acquisition Settings
[0153] Data acquisition instrument parameter settings: sampling frequency: 100kHz, acquisition duration: 30s, acquisition channels: pressure signal, temperature signal, target line on / off signal (channel 1, channel 2); all channels are triggered for acquisition synchronously to ensure time axis consistency.
[0154] Step β6, Ignition Test
[0155] The electric ignition head at the center of the tablet is ignited by a 12V DC power supply, and the synchronous electric ignition signal serves as the zero-time reference (t=0) for data acquisition. The combustion process continues until the tablet is completely burned out. Data acquisition is then turned off, and the igniter is allowed to cool naturally to room temperature for 30 minutes while the gas production is tested.
[0156] Step β7, Repeat the test
[0157] Replace with another set of tablets that passed the initial inspection, and repeat steps β2 to β6, performing three parallel tests on each set of samples. Allow at least 30 minutes between each test to ensure the burster cools to room temperature and the cavity is purged of residual gas. The test results are shown in Table 1.
[0158] Table 1. Statistical results of the effect of copper amidourea nitrate of different particle sizes on the performance of gas generators.
[0159]
[0160] The "burning rate of 6.86 MPa mm / s" represents the linear velocity of the propellant charge under a specific test condition of 6.86 MPa, expressed in millimeters per second (mm / s). The "pressure index n" is a core parameter in the field of energetic materials (propellants, gunpowder) that measures the sensitivity of burning rate to changes in ambient pressure. Depending on the value of n, the combustion characteristics of the propellant charge are completely different.
[0161] n=0: Burning rate is independent of pressure (ideal state, combustion is extremely stable).
[0162] n<1 (usually 0.2~0.7): the burning rate increases with increasing pressure, but the rate of increase decreases (the ideal range for most airbag propellants).
[0163] n=1: Burning rate is directly proportional to pressure (increasing linearly).
[0164] n>1: The burning rate increases exponentially with increasing pressure (which can easily lead to uncontrolled deflagration due to pressure, a dangerous zone).
[0165] In automotive airbags, a lower pressure index (n) is better. This is because the internal pressure of the airbag fluctuates drastically at ignition. If n is too high, the combustion rate will fluctuate wildly with the pressure fluctuations, leading to unstable airbag inflation. If n is low, even with pressure fluctuations, the combustion rate remains relatively constant, resulting in smoother, more reliable, and safer airbag inflation. In this embodiment of the invention, the pressure index of ultrafine copper amidine urea nitrate (D50 = 3~6μm) is 0.579. Although slightly higher than the existing technology's 0.374, this value is still far below the safety warning value of 1.0, falling within the industrial safe usage range for automotive gas generators (typically requiring n < 0.7). More importantly, at this pressure index, the combustion rate is increased by 6.6 mm / s compared to the existing technology, and the combustion temperature is reduced by 139 K, indicating that this invention achieves significant optimization of combustion rate and combustion temperature performance at the cost of acceptable pressure sensitivity.
[0166] As shown in Table 1, when 10% copper amidocyanate is added, the burning rate gradually increases as the particle size of copper amidocyanate decreases, and the burning temperature gradually decreases as the particle size of copper amidocyanate decreases. Moreover, the tablet density, mass gas production and volume gas production remain stable with very little change.
[0167] Specifically:
[0168] (1) Significantly improved burning rate. When the particle size of copper amidine urea nitrate decreased from 30-50 μm to 3-6 μm, the burning rate gradually increased from 13.9 mm / s to 20.5 mm / s, an increase of 6.6 mm / s. Compared with the blank formulation (serial number 1, 12.7 mm / s) without the addition of copper amidine urea nitrate, the burning rate increased by 7.8 mm / s. This is particularly low. In US Patent US6602365B1, 30% copper amidine urea nitrate is required to achieve a burning rate of 16.7 mm / s, while the present invention achieves a burning rate of 20.5 mm / s with only 10% of the ultrafine product (D50=3-6 μm), which is 3.8 mm / s higher than the burning rate under the 30% addition of the patent. This indicates that the ultrafine copper nitrate amidine urea prepared by the method of the present invention can achieve a combustion rate level that surpasses that of the prior art at higher addition amounts with only one-third of the addition amount, thus significantly reducing the amount of effective components used.
[0169] (2) Significantly reduced combustion temperature. When the particle size of copper amidocyanate decreased from 30-50 μm to 3-6 μm, the combustion temperature gradually decreased from 1805 K to 1666 K, a reduction of 139 K. Compared with the blank formulation without copper amidocyanate (1868 K), the combustion temperature decreased by 202 K. The reduction in combustion temperature will directly reduce the generation of harmful gases such as nitrogen oxides (NOx) in the gaseous products, improving the environmental friendliness and safety of the gas generator.
[0170] (3) Stable gas production. As the particle size of copper amidine urea nitrate decreased from 30-50 μm to 3-6 μm, the volumetric gas production remained stable between 0.0554-0.0560 mol / mL, the mass gas production remained stable between 2.83-2.96 mol / 100g, and the tablet density remained stable between 1.90-1.96 g / cm³. None of these three parameters showed a significant decrease due to particle size reduction. This effectively overcomes the technical defect in the existing technology where the gas production decreases due to increased CuGUN addition, and achieves synergistic optimization of "high performance + low addition + stable gas production".
[0171] Based on the above test results, Example 1 (D50=3~6μm) is the preferred embodiment of the present invention. It can achieve the best combustion rate improvement and combustion temperature reduction effect with an addition of 10%, while maintaining the gas production without decreasing, and has the best overall performance.
[0172] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit them. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the present invention.
Claims
1. A method for synthesizing ultrafine amidine urea copper nitrate, characterized in that, Includes the following steps: Step 1: Dissolve copper nitrate trihydrate in deionized water, add dispersant, and stir at 60~70℃ to obtain aqueous phase A of copper nitrate; Dicyandiamide was dissolved in deionized water and dissolved with ultrasonic assistance at 60-70℃. After filtration to remove impurities, dicyandiamide aqueous phase B was obtained. Step 2: Mix isoparaffin solvent oil, Span80 and Tween80, and stir at 60℃~70℃ until transparent and homogeneous to form an oil phase-surfactant system; add the dicyandiamide aqueous phase B to the system, stir to form a dicyandiamide-loaded reverse microemulsion M2, and keep it at 60℃~70℃ for later use. Separately, take isoparaffin solvent oil, Span80 and Tween80 and mix them. Stir at 60℃~70℃ until transparent and homogeneous to form an oil phase-surfactant system. Add the copper nitrate aqueous phase A to the system and stir to form a copper nitrate-loaded reverse microemulsion M1. Keep it at 60℃~70℃ for later use. Step 3: Place the reverse microemulsion M2 in a constant temperature water bath at 60~70℃, and add the reverse microemulsion M1 dropwise to the reverse microemulsion M2 under stirring to carry out the coordination reaction. After the addition is complete, the reaction system is obtained. Continue to keep the reaction system warm and stir for 30min~60min. Step 4: Heat the reaction system to 90℃~95℃, and then keep it at this temperature to carry out the hydrolysis reaction; Step 5: After the hydrolysis reaction is completed, cool down, add anhydrous ethanol to the reaction system to break the emulsion, separate by centrifugation, and then filter to obtain the first filter cake. Wash the first filter cake to obtain the second filter cake. Step 6: Vacuum dry the second filter cake to obtain the ultrafine copper nitrate amidine urea product.
2. The method for synthesizing ultrafine amidine urea copper nitrate according to claim 1, characterized in that: In step 1, the mass ratio of copper nitrate trihydrate to deionized water is 1.00 g: 1.00~2.40 mL; the dispersant is PEG-400, or a combination of PEG-400 and PVP-K30, and the amount of dispersant used is 2.5%~14.0% of the mass of copper nitrate trihydrate; the mass ratio of dicyandiamide to deionized water is 1.00 g: 6.35~12.80 mL. In step 2, the isoparaffin solvent oil is IsoparG; the volume ratio of IsoparG, Span80, Tween80, and dicyandiamide aqueous phase B in the reverse microemulsion M2 is 130.00~135.00mL: 2.80~3.20g: 1.00g: 9.50~16.00mL; The volume ratio of IsoparG, Span80, Tween80, and copper nitrate aqueous phase A in the reverse microemulsion M1 is 130.00~135.00mL: 2.80~3.20g: 1.00g: 13.00~14.50mL.
3. The method for synthesizing ultrafine amidine urea copper nitrate according to claim 1, characterized in that: In step 5, the washing of the first filter cake specifically involves sequentially washing the first filter cake with anhydrous ethanol, anhydrous isopropanol, and deionized water in a gradient manner.
4. The method for synthesizing ultrafine amidine urea copper nitrate according to claim 2, characterized in that: In step 3, the stirring speed of the coordination reaction is 400 rpm to 700 rpm, and the dropping rate of the reverse microemulsion M1 is 0.2 mL / min to 0.5 mL / min; In step 4, the heating rate is 6℃ / h ~ 10℃ / h, the hydrolysis reaction temperature is 92℃, and the holding time is 5h ~ 7h; In step 5, when demulsifying, the amount of anhydrous ethanol added is 8% to 12% of the total volume of the reaction system, the stirring speed during demulsification is 200 rpm to 300 rpm, and the duration is 15 min to 25 min; the centrifugation speed is 6000 rpm to 8000 rpm, and the duration is 10 min to 15 min. In step 6, the vacuum drying temperature is 60℃~70℃, the vacuum degree is 0.08 MPa~0.09 MPa, and the drying time is 6h~10h.
5. The method for synthesizing ultrafine amidine urea copper nitrate according to claim 3, characterized in that: In step 5, the gradient washing specifically involves: Step 5a: Wash with anhydrous ethanol 2-4 times, then filter to remove anhydrous ethanol; Step 5b: Wash 2-3 times with anhydrous isopropanol, then filter to remove the anhydrous isopropanol; Step 5c: Rinse once with deionized water, and then perform vacuum filtration to obtain a second filter cake, wherein the moisture content of the second filter cake is ≤5%.
6. The method for synthesizing ultrafine amidine urea copper nitrate according to claim 4, characterized in that: In steps 2 and 3, by controlling the following parameter combinations, step 6 obtains ultrafine copper nitrate products with different particle size ranges: Step 2 controls the water-oil ratio of reverse microemulsion M1 to be 0.100 and the water-oil ratio of reverse microemulsion M2 to be 0.071~0.
072. Simultaneously, Step 3 controls the stirring speed of the coordination reaction to be 700 rpm and the dropping acceleration rate of reverse microemulsion M1 to be 0.5 mL / min. Step 6 obtains an ultrafine copper nitrate product with a D50 of 3~6 μm. Step 2 controls the water-oil ratio of reverse microemulsion M1 to be 0.100 and the water-oil ratio of reverse microemulsion M2 to be 0.095~0.
096. Meanwhile, in step 3, the stirring speed of the coordination reaction is controlled at 500 rpm and the dropping rate of reverse microemulsion M1 is controlled at 0.3 mL / min. In step 6, an ultrafine copper nitrate product with a D50 of 10~20 μm is obtained. Step 2 controls the water-oil ratio of reverse microemulsion M1 to be 0.100 and the water-oil ratio of reverse microemulsion M2 to be 0.119~0.
121. Simultaneously, Step 3 controls the stirring speed of the coordination reaction to be 400 rpm and the dropping acceleration rate of reverse microemulsion M1 to be 0.2 mL / min. Step 6 obtains an ultrafine copper nitrate product with a D50 of 20~30 μm. The water-oil ratio is the volume ratio of water to isoparaffin solvent oil in reverse microemulsion M1 or reverse microemulsion M2. The water-oil ratio is controlled by changing the amount of deionized water added in step 1 and the amount of isoparaffin solvent oil added in step 2.
7. An ultrafine copper nitrate amidine urea, characterized in that, It was prepared by the synthesis method of ultrafine amidourea copper nitrate as described in any one of claims 1 to 6.
8. The ultrafine amidine urea copper nitrate according to claim 7, characterized in that: Its D50 particle size is 3~30μm, the particle size distribution PDI≤0.35, and the particle morphology is irregular particles.
9. The use of the ultrafine copper amidocyanate nitrate as described in claim 7 or 8 in automotive airbag gas generators.
10. The application of the ultrafine copper amidine nitrate according to claim 9 in automotive airbag gas generators, characterized in that, The application method of ultrafine amidourea copper nitrate in automotive airbag gas generators is as follows: The ultrafine copper amidocyanate nitrate is mixed with guanidine nitrate, basic copper nitrate, α-Al2O3, and magnesium stearate, and then compressed into tablets to obtain a tablet for use in automotive airbag gas generators. In the tablet for automotive airbag gas generators, the mass fraction of ultrafine copper amidocyanate nitrate is 10%, the mass fraction of guanidine nitrate is 42.07%, the mass fraction of basic copper nitrate is 44.93%, the mass fraction of α-Al2O3 is 3%, and the amount of magnesium stearate added is 0.2% of the total mass of the main formulation of ultrafine copper amidocyanate nitrate nitrate, guanidine nitrate, basic copper nitrate, and α-Al2O3.
Citation Information
Patent Citations
A method for preparing a copper salt complex of amidine nitrate
CN109836358B
Gas generation via metal complexes of guanylurea nitrate
US6602365B1